Az ut pictura poesis velencei mestere: Giovan Mario Verdizzotti és állatmeséi - Vígh, Éva (Antikvitás & Reneszánsz, 2018)
The paper (The Venetian master of the ut pictura poesis: Giovan Mario Verdizzotti and his animal fables) is dedicated to a little-known author of the Italian Renaissance: Giovan Mario Verdizzotti, poet and painter, a pupil of Titian. His masterpiece (Cento favole morali / Hundred moral fables) belongs to the rich literature of the sixteenth-century fables, whose particularity lies in the fact that the illustrations were made by the author himself thus realizing in one person the principle of the Horatian ut pictura poesis. The paper analyzes some fables demonstrating the harmony between the story and the drawing, and at the same time compares the structure and style of his woodcuts with those of the collection of Faerno and Pavesi, declared sources of our author.